2019
DOI: 10.3390/w11020198
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Soil Water Content and Evapotranspiration in Relation to Precipitation Pulses within Desert Steppe in Inner Mongolia, China

Abstract: Neither single nor discontinuous hydrological observation data can truly reflect periodic changes in soil moisture under natural conditions or interrelationships between various water sources. Therefore, in this study, precipitation pulse characteristics and variations in the soil water content (SWC) and actual evapotranspiration (ETa) in relation to pulses are explored through a field multi-water continuous observation system set in desert steppe in Inner Mongolia, China. A comparison between precipitation ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In addition, soil moisture may affect the atmospheric condition by directly influencing evaporation and latent heat (Mahrt and Ek, 1984), and soil moisture can also affect the prediction of a forecast model for two to three weeks or more (Walker and Rowntree, 1977). Therefore, it is of great significance to use soil moisture data properly a the land-surface model and to understand the mechanisms underlying the interaction between soil moisture and the atmosphere (Pan and Mahrt, 1987;Chen et al, 1997;Gaertner et al, 2010;Seneviratne et al, 2010;Vereecken et al, 2014;Li et al, 2019;Shi et al, 2019;Song et al, 2019).…”
mentioning
confidence: 99%
“…In addition, soil moisture may affect the atmospheric condition by directly influencing evaporation and latent heat (Mahrt and Ek, 1984), and soil moisture can also affect the prediction of a forecast model for two to three weeks or more (Walker and Rowntree, 1977). Therefore, it is of great significance to use soil moisture data properly a the land-surface model and to understand the mechanisms underlying the interaction between soil moisture and the atmosphere (Pan and Mahrt, 1987;Chen et al, 1997;Gaertner et al, 2010;Seneviratne et al, 2010;Vereecken et al, 2014;Li et al, 2019;Shi et al, 2019;Song et al, 2019).…”
mentioning
confidence: 99%
“…Precipitation is the most important factor limiting grassland production in arid regions (Song et al, 2019). We found that, with an increase in precipitation, the abundance, density, biomass, diversity and seed yield of the AGV increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of global climate change, there will be fewer precipitation events in certain geographic regions yet larger per‐event rainfall volumes, and the frequency of extreme precipitation events will also increase globally (Intergovernmental Panel on Climate Change, 2013). Precipitation correlates positively with grassland productivity (Gamoun, 2016; Song et al, 2019). Changes in precipitation patterns can have a notable impact on the structure and species dynamics of grassland ecosystems, as precipitation is the main limiting factor of grassland productivity, especially in semiarid and arid regions (Noy‐Meir, 1973; Reynolds et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…x bi advancement distance of the intersection point between the transmission zone and the wetting zone (m) x ci advancement distance of the intersection point of two linear functions in the wetting zone (m) x i advancement distance of the WF (m) x T water advancement distance at the top of the PVC column (m) y [1][2][3][4] parameters that described relationship between T t and θ Greek letters…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…The unsaturated zone of the earth's surface is an important link between the atmosphere and deeper soil profiles. Water movement and its distribution within the unsaturated zone determine the physical and hydrological properties of the soil medium and its utility in many socio-economic activities such as environmental sustainability, geo-hazards management, stability of marine dike, and beach erosion [1][2][3][4]. The unsaturated ground surface is also the most important homeland for insects, and the activities of these insects are changing water infiltration model [5].…”
Section: Introductionmentioning
confidence: 99%